The Multifaceted Roles of RCC1 in Tumorigenesis - Ren, Xuanqi; Jiang, Kai; Zhang, Feng (Frontiers in Molecular Biosciences, 2020)
RCC1 (regulator of chromosome condensation 1) is the only known guanine nucleotide exchange factor of Ran, a nuclear Ras-like G protein. RCC1 combines with chromatin and Ran to establish a concentration gradient of RanGTP, thereby participating in a series of cell physiological activities. In this review, we discuss the structure of RCC1 and describe how RCC1 affects the formation and function of the nuclear envelope, spindle formation, and nuclear transport. We mainly focus on the effect of RCC1 on the cell cycle during tumorigenesis and the recent research progress that has been made in relation to different tumor types.